Agrarian Protest and Provincial Politics: Prince Edward Island and the 1971 National Farmers Union Highway Demonstration - O’Connor, Ryan (Acadiensis, 2008)
Abstract During ten days in August 1971 Prince Edward Island farmers, led by the local chapter of the National Farmers Union, staged high-profile public protests against the provincial government’s neglect of family farm issues and its promotion of economic rationalization and modernization as exemplified in the government’s 1969 Comprehensive Development Plan. While these protests did not stop the trend towards farm abandonment, they did manage to put the concerns of small farmers on the political agenda and dampen the government’s enthusiasm for development planning that ignored small producers. The result was a consultation process between the government and small farmers and the government’s 1972 Family Farm Development Policy.